The Problem with Changing the Folk Law of Bullying: A look at Folk Law and its relation to the Bullying of Teachers in Newfoundland and Labrador - Learning, Jeffery (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2019)
In this paper I will explore the crucial relationship between folk law and bullying in an effort to explain some of the most problematic pieces being left out of current anti-bullying solutions in Newfoundland and Labrador. Using bullying examples from interviews with teachers from across the province of Newfoundland and Labrador collected for my dissertation, “Dialogues of Dominance: Narrative, Occupational Folklore, & the Bullying of Public-School Teachers”, I will attempt to show how insidious the bullying problem really is. I will focus on three key barriers facing school anti-bullying movements in Canada today: the exploitation of folk law; the definitional confusion of ‘bullying’; and the creation and maintenance of a triviality barrier that obfuscates bullying when it happens between adults. I will then use these problems to explain why it falls to the use of folklore to curb this behaviour, and how folkloristics can help with the development of stronger anti-bullying campaigns.